Why Did They Fail? Investigating The Eight Invalid Dimensions of Patient Safety Culture: Mixed Method Research - Felicia Setiawan; Ferdi Antonio (Jurnal Keperawatan Indonesia, 2024)
Resistance to adopting patient safety culture practices or technologies can hinder improvements in patient safety. This study contributes to enhancing the understanding of patient safety culture (PSC) assessment by identifying the specific factors that render some PSC dimensions invalid and offering actionable recommendations for improvement in healthcare settings. Primary data were gathered using a mixed method of explanatory sequential design, with quantitative data collection and analysis followed by qualitative data collection and analysis. The study was conducted in the leading Private Hospital XYZ, one of the private hospital groups internationally accredited with Joint Commission International with a 110-patient bed capacity. Among the 12 dimensions, only feedback communication about error, handoffs and transitions, and teamwork across units were determined to be valid and reliable. Therefore, eight dimensions, including communication openness, continuous improvement, frequency of error reported, management support, overall patient safety, supervisor/manager expectation, and staffing were explored further through a focus group discussion (FGD). Delving into quantitative and qualitative insights has identified critical nuances that extend beyond mere quantitative metrics. The qualitative insights gleaned from healthcare professionals through the FGD illuminated the nuanced human aspects of safety culture that traditional measurements may overlook. Keywords: anonymous reporting, management of communication, mixed method, patient safety culture   Abstrak Mengapa Penilaiannya Gagal? Menyelidiki 8 Dimensi yang Tidak Valid dari Budaya Keselamatan Pasien: Penelitian Mixed Method. Penolakan untuk mengadopsi praktik atau teknologi budaya keselamatan pasien dapat menghambat peningkatan keselamatan pasien. Penelitian ini bertujuan untuk meningkatkan pemahaman tentang penilaian budaya keselamatan pasien (Patient Safety Culture [PSC]) dengan mengidentifikasi faktor-faktor spesifik yang menyebabkan beberapa dimensi PSC tidak valid, dan memberikan rekomendasi yang dapat ditindaklanjuti untuk perbaikan di lingkungan pelayanan kesehatan. Data primer dikumpulkan dengan menggunakan mixed method of explanatory sequential design, dengan pengumpulan dan analisis data kuantitatif diikuti dengan pengumpulan dan analisis data kualitatif. Penelitian dilakukan di Rumah Sakit Swasta terkemuka XYZ, salah satu grup rumah sakit swasta yang terakreditasi internasional Joint Commission International dengan kapasitas 110 tempat tidur pasien. Diantara 12 dimensi, hanya dimensi feedback communication about error, handoffs and transitions, dan teamwork across units, yang memenuhi syarat valid dan reliabel. Oleh karena itu, 8 dimensi yaitu communication openness, continuous improvement, frequency error reported, management support, overall patient safety, supervisor/manager expectation, dan staffing didalami lebih lanjut dalam focus group discussion (FGD). Melalui penggalian wawasan kuantitatif dan kualitatif, telah teridentifikasi deskripsi penting yang melampaui metrik kuantitatif. Wawasan kualitatif yang diperoleh dari para profesional di bidang kesehatan melalui FGD telah menyingkap aspek-aspek budaya keselamatan yang bernuansa manusiawi, yang mungkin terlewatkan oleh pengukuran tradisional. Kata Kunci: budaya keselamatan pasien, manajemen komunikasi, metode campuran, pelaporan anonim